Learning to save the world : global health pedagogies and fantasies of transformation in Botswana - Brada, Betsey Behr, 1976- (Cornell University Press, 2023)
"Using data from southeastern Botswana, efforts to educate HIV-positive children about their treatment are contrasted with global health rotations for American medical students in order to demonstrate that 'global health' is not a set of problems or institutions, but rather an imaginative practice that hinges on a range of pedagogies"-- Provided by publisher.
Keywords: AIDS (Disease) -- Treatment -- Social aspects -- Botswana.; AIDS (Disease) in children -- Social aspects -- Botswana.; Medical anthropology -- Botswana.; Public health -- Anthropological aspects -- Botswana.; Medical education -- Social aspects -- Botswana.; Health education -- Social aspects -- Botswana.; Transcultural medical care -- Botswana.; World health -- Social aspects.; Sida -- Traitement -- Aspect social -- Botswana.; Santé publique -- Aspect anthropologique -- Botswana.; Éducation sanitaire -- Aspect social -- Botswana.; Services transculturels de santé -- Botswana.; Santé mondiale -- Aspect social.; SOCIAL SCIENCE / Anthropology / Physical; AIDS (Disease) in children -- Social aspects; Health education -- Social aspects; Medical anthropology; Medical education -- Social aspects; Public health -- Anthropological aspects; Transcultural medical care; World health -- Social aspects; Botswana; Botswana.; United States of America, USA.; Social & cultural history.; Ethnic studies.; Anthropology.; Health and Wellbeing.; Electronic books.